PENYULUHAN DAN PELATIHAN TRICHODERMA SP. SECARA MASSAL DARI BERBAGAI MEDIA SEBAGAI REKOMENDASI PENCEGAHAN PENYAKIT LAYU FUSARIUM PADA TANAMAN PISANG - Iry, Aloysia Wihelmina; Yovita Yasintha Bolly; Yuyun Wahyuni (PAKDEMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
This research aims to find out the process of making Trichoderma sp and the fastest growth process using several experimental planting media. Recently, in Sikka district, banana plants in almost all areas have been affected by fusarium wilt disease. And one natural alternative to control fusarium wilt disease is to use Trichoderma sp. Trichoderma sp is also very cost-effective and environmentally friendly. The method used in this research is the observation method. Meanwhile, secondary data is usually stored in documents that have been archived. Data sources are usually obtained from journals, previous reports, company websites and other sources. This counseling and training was provided to employees from the East Flores Regency Plantation Service. From the results of the training on mass production of Trichoderma Sp, the best results were obtained for the growth of Trichoderma Sp using Husk and Rice media on the 7th day after the manufacturing process, the growth was already visible. For bran and rice, growth is not yet perfect because there is rot in certain parts. After 2 weeks of growth, Trichoderma sp can be harvested. Based on the results of this Trichoderma sp propagation training, it can be concluded that the media used for Trichoderma sp propagation have different effectiveness and the most effective media in the propagation process carried out in this training for the most perfect development and growth is using husks and rice and also very recommended for controlling fusarium wilt disease.